CAGE‐prox: A Unified Approach for Time‐Resolved Protein Activation in Living Systems. Issue 6 (24th June 2021) - Wang, Jie; Liu, Yuan; Liu, Yanjun; Wang, Chu; Chen, Peng R.
Abstract: Temporal activation of proteins of interest (POIs) offers a gain‐of‐function approach to investigate protein functions in dynamic biological processes. Fusion of photo/chemical‐switchable proteins to a POI, or site‐specific blockage/decaging of catalytic residue(s) on a POI, are the most widely utilized strategies for selective protein activation. These methods, however, either lack generality (e.g., active site decaging) or would modify the POI with a bulky tag (e.g., genetic fusion). Recently, a computationally aided and genetically encoded proximal decaging strategy (CAGE‐prox) has been developed for time‐resolved photoactivation of a broad range of proteins in living systems. In contrast to the direct decaging of the active site of a POI, CAGE‐prox relies on a unified caged amino acid that can be anchored in proximity to a protein's functional site for temporal blockage of its activity until rescued by photo/chemical decaging. In order to identify the optimal site for photo‐caged unnatural amino acid insertion, which is key for the effective blockade and re‐activation of the POI, a computational algorithm was developed to screen all possible positions in close proximity to the functional site that would enable turning off/on protein activity via caging/decaging operations. Here, we describe the CAGE‐prox strategy, from in silico design to experimental validation, and provide various examples of its application. © 2021 Wiley Periodicals LLC Basic Protocol 1 : In silico design and experimental validation of CAGE‐prox Basic Protocol 2 : Orthogonal activation of a POI by CAGE‐prox while minimizing the activity from the endogenous protein Basic Protocol 3 : CAGE‐prox‐enabled, time‐resolved proteomics for the identification of substrates of a proteolytic enzyme Basic Protocol 4 : Controlled activation of protein‐based prodrugs for tumor therapy